The moderating effect of psychological capital on the relationship between nurses’ perceived workplace bullying and emotional exhaustion: a cross-sectional study - Xiao Peng; Jing Ma; Ying Chen; Ying Han; Hong Zhou; Aiping Gong; Fang Peng; Xinzhang Sun; Xingfen Wang; Xunya Xiong; Li Li; Mengting Huang; et al. (BMC Nursing)
Abstract Background Workplace bullying (WPB) is common in nursing profession, leading to adverse effects on nurses’ health and teamwork. Although it has been suggested that psychological capital (PsyCap) could potentially moderate the relationship between WPB and emotional exhaustion, there is currently a lack of direct empirical evidence supporting this claim. Therefore, this study aims to examine how PsyCap moderates the relationship between WPB and emotional exhaustion in nurses. Methods A cross-sectional study was carried out involving 1068 nurses using a general information questionnaire, Negative Acts Questionnaire-Revised, Psychological Capital Questionnaire-Revision, and emotional exhaustion subscale of the Chinese version of Maslach Burnout Inventory-General Survey. The PROCESS macro was utilized to examine the moderating effect of PsyCap. Results WPB led to emotional exhaustion among nurses (β = 1.488, P < 0.001), and PsyCap moderated this positive relationship (β = 0.300, P < 0.001). The group with high PsyCap exhibited lower levels of emotional exhaustion. However, as the perceived WPB increased, the disparity in emotional exhaustion between the high and low PsyCap groups diminished. Conclusions WPB significantly contributes to nurses’ emotional exhaustion. PsyCap mitigates this impact, but this effect is limited in organizations with high WPB. it is recommended that nursing managers mitigate the detrimental impact of WPB on nurses’ emotional well-being by both strengthening nurses’ individual PsyCap and implementing comprehensive strategies to reduce WPB behaviors.